KINERJA LEMBAGA EKONOMI MASYARAKAT SEJAHTERA (LEMS) DALAM PENGEMBANGAN KAPASITAS PETANI KAKAO DI KABUPATEN KONAWE - Ulyas niati (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The research was carried out at the Konawe District Economic Community Prosperous Andomesinggo Society with the aim of: 1) To determine the performance of the Prosperous Com-munity Economic Institution (LEMS) on capacity building of cocoa farmers in Andomesinggo Village, Besulutu District, Konawe Regency; 2) To find out the capacity of cocoa farmers with the existence of the Prosperous Economic Community Institution in Andomesinggo Village, Besulutu District, Konawe Regency; 3) To find out the relationship between the performance of the Prosperous Community Economic Institution (LEMS) and the capacity of cocoa farmers in Andomesinggo Village, Besulutu District, Konawe District. The results showed that: 1) The Prosperous Economic Institution Performance was classified as good with a percentage of 80%. The Prosperous Society has succeeded in developing the capacity of cocoa farmers in Andomesinggo Village. 2) The working capacity of farmers assisted by the Prosperous Community Economic Institution is still in the good category or shows that farmers have succeeded or are able to increase their capacity including: a) Cultivation Technique Ability, b) Managerial Ability c) Ability to Increase Farming, d) Ability to Cooperate, e) Ability Adaptation. 3) The Performance of Prosperous Community Economic Institutions and the capacity of farmers indicates a positive and close relationship and the research hypothesis which says that the performance of the Prosperous Community Economic Institution is significantly related to the work capacity of farmers, can be accepted at a 95% confidence level.